Examining The Impact of Customer Satisfaction and Brand Image toward Consumer Loyalty on Bank Syariah Indonesia - Nofirda, Fitri Ayu; Susanto, Perengki (Jurnal Manajemen Teknologi, 2024)
Abstract. Bank Syariah Indonesia is a financial institution whose principal business is to provide credit and services in payment and money circulation that operates in accordance with sharia principles. This research is intended to see the role of customer satisfaction and brand image mediating customer engagement on Bank Syariah Indonesia customer loyalty. Through the purposive sampling method, the number of samples is determined to be at least 120 respondents. Data collection using questionnaire dissemination. Structural Equation Modeling (SEM- AMOS) analysis technique version 26 was used in this study. These results show that Customer Satisfaction has a significant effect on Customer Loyalty, Brand Image has a significant effect on Customer Loyalty, Customer Engagement has a significant effect on Customer Loyalty. Customer Satisfaction has a significant effect on Customer Loyalty through Customer Engagement, and Brand Image has a significant effect on Customer Loyalty through Customer Engagement. Keywords: Customer satisfaction, brand image, customer engagement customer loyalty   Abstrak. Bank Syariah Indonesia suatu lembaga keuangan yang usaha pokoknya memberikan kredit dan jasa-jasa dalam pembayaran serta peredaran uang yang beroperasi disesuaikan dengan prinsip-prinsip syariah. Penelitian ini dimaksudkan guna melihat peran customer satisfaction dan brand image memediasi customer engagement terhadap loyalitas nasabah Bank Syariah Indonesia. Melalui purposive sampling method ditentukan jumlah sampel yaitu minimal 120 responden. Pengumpulan data menggunakan penyebaran kuisioner. Teknik analisis Structural Equation Modeling (SEM-AMOS) versi 26 digunakan pada penelitian ini. Hasil tersebut menunjukkan Customer Satisfaction berpengaruh signifikan terhadap Loyalitas Nasabah, Brand Image berpengaruh signifikan terhadap Loyalitas Nasabah, Customer Engagement berpengaruh signifikan terhadap Loyalitas Nasabah. Customer Satisfaction berpengaruh signifikan terhadap Loyalitas Nasabah melalui Customer Engagement, dan Brand Image berpengaruh signifikan terhadap Loyalitas Nasabah melalui Customer Engagement. Kata kunci: Customer satisfaction, brand image, loyalitas nasabah, customer engagement.